Efectos del uso de fitasa en la alimentación de gallinas ponedoras. - Yépez Montes, Erbilen Rossmary (2022)
Exogenous enzymes improve bird nutrition through phytate degradation releasing phosphorus and minerals. The main function is to access the cell walls of the fibrous ingredients and release the nutrients that are encapsulated, thus making them accessible, increasing the availability of nutrients and reducing microbial proliferation. The research was carried out with the objective of evaluating the effect of the use of phytase in the feeding of laying hens. The research methodology was carried out through a bibliographic review in scientific journals, books, articles published on websites. Inductive, deductive and analysis methods are used. According to data published by the National Institute of Statistics and Censuses INEC (2021) in the Survey of Surface and Continuous Agricultural Production (ESPAC): "In the poultry sector, 7.8 million birds were registered that are raised in the field, which represents 82.9% and 37.8 million in poultry farms shows 17.1%". the inclusion of phytase, in doses of 350 or 450 U/kg, increases the bioavailability of vegetable phosphorus, which guarantees an adequate supply of Pd (0.26 and 0.32%), sufficient for optimal productive performance and increase in egg weight. supplementation of 60 ppm of phytase enzyme in diets of Isa Brown laying hens from 58 to 67 weeks of age improved flock uniformity based on live weight. Phytase represents an alternative for poultry producers, because including this enzyme, cheaper ingredients can be used in the diet, which allow lower costs without affecting the productive behavior of laying hens and the environment.